Análisis de los datos de las fichas técnicas del mantenimiento de alumbrado público para el diseño de un sistema de gestión de calidad bajo la norma internacional iso 9001, en la Empresa Eléctrica Cotopaxi S.A. dentro de su área de concesión en el año 2014 - Castro Yánez, Mauro Stalin (2015)
The present researching has a main proposal to know the real Service customer Public Energy and to implement a gestion system; it will give to improve the conditions today and in the future, joking account in the actuality it permits to give a good Service when damage occurs in the public energy. The analysis was doing inside the Cotopaxi Enterprise (S.A) ELEPCO, It has 30.473 Lights approximately. With different features Cotopaxi Electrical Enterprise (ELEPCO S.A.), with a development and implementation in the maintenance gestion system in the public energy, has an objective to evaluate, distinguished and doing maintenance Works, and by analyzing data sheets Public Lighting design preventive maintenance according to compliance with the lifetime of the installed material, thereby reducing service times repair, increasing efficiency and improving the perception of better attention from users.